Optimization of phosphorus removal from reject water of sludge thickening and dewatering process through struvite precipitation. Issue 33 (14th July 2016) - Ren, Weichao; Zhou, Zhen; Wan, Li; Hu, Dalong; Jiang, Lu-Man; Wang, Luochun
Abstract: Chemical precipitation using magnesium salt is an effective technology for recovering phosphorus and ammonium nitrogen from wastewater. Effects of pH, Mg/P ratio, stirring rate, and seed crystal (SC) dosage on phosphate removal efficiency (PRE) and average particle diameter (APD) of precipitates were investigated for reject water from sludge thickening and dewatering process in municipal wastewater treatment. Response surface methodology was applied to understand the significance and the interactive effects of reaction factors. The increases in Mg/P ratio, stirring rate, and SC dosage were in favor of phosphate removal from reject water. pH is the dominant factor for phosphate removal by magnesium, followed by Mg/P and stirring rate, while SC dosage has the least effect on PRE and APD. Kinetic analysis showed that both pH regulation and SC addition could accelerate the reaction rate. The optimum conditions were obtained at pH 10.4, Mg/P of 2.0, stirring rate of 150 rpm, and SC dosage of 26.7 mg/L, with PRE of 95.9%, APD of 104 μm, and final mass of precipitate of 936.3 mg/L. X-ray diffractometer analysis revealed that the increase in pH resulted in the increase in crystallinity and the conversion of struvite to calcium pyrophosphate, and the precipitates of reject water were struvite at pH < 10.5.